2010
DOI: 10.1002/cbf.1663
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Hippophea rhamnoides L. extract reduce nicotine‐induced oxidative stress in rat heart

Abstract: The effects of vitamin E and Hippophea rhamnoides L. extract (HRe-1) on nicotine-induced oxidative stress in rat heart were investigated. There were eight rats per group and supplementation period was 3 weeks. The groups were: nicotine [0.5 mg kg(-1)day(-1), intraperitoneal (i.p.)]; nicotine plus vitamin E [75 mg kg(-1)day(-1), intragastric (i.g.)]; nicotine plus HRe-1 (250 mg kg(-1)day(-1), i.g.); and the control group (receiving only vehicles). Nicotine increased the malondialdehyde level, which was prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…In addition, lipid peroxides may inhibit protein synthesis, block macrophage function, and alter chemotactic activity. [4112627]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid peroxides may inhibit protein synthesis, block macrophage function, and alter chemotactic activity. [4112627]…”
Section: Discussionmentioning
confidence: 99%
“…For example, Geetha et al (2008) showed that the sea buckthorn leaf extract has a significant hepato-protective effect which was attributed to the antioxidant compounds present in the extract. Similarly, Gumustekin et al (2010) studied the effects of nicotine-induced oxidative stress in rat heart with vitamin E and sea buckthorn extract. The authors showed that supplementation of extract increased superoxide dismutase and glutathione S-transferase activities, which may be contributing to the prevention of nicotine-induced oxidative stress in rat heart.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In addition, Vitamin E has been shown to be cardioprotective against peroxidative damage induced by tobacco smoke. [1415] Ozone is a very reactive gas and is well known as a potent oxidant. [16] However, recent studies have clearly shown that a small and precisely ozone dose can induce upregulation of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%